Death penalty - Nardo, Don, 1947- (San Diego, CA : Lucent Books, 1992)
Discusses various aspects of the debate over capital punishment, including its use as a deterrent to crime, discrimination and the death penalty, juveniles on death row, and the morality of this sentence.
Includes bibliographical references (p. 89-91) and index.
Wilson's Junior High School.
7.7
5-8
7-9
Keywords: Capital punishment -- United States -- Juvenile literature; Capital punishment; Capital punishment